2020
DOI: 10.1590/1516-4446-2019-0593
|View full text |Cite
|
Sign up to set email alerts
|

Early maladaptive schemas and harm avoidance as mediating factors between early life stress and psychiatric symptoms in adults

Abstract: Objective: This study investigated how factors of temperament and early maladaptive schemas predict psychiatric symptoms, as well as how they mediate the relation between early life stress and psychiatric symptoms in adults. Methods: A cross-sectional study was conducted with a sample of 200 university students. Data was collected through a sociodemographic questionnaire, the Adult Self-Report Inventory, the Childhood Trauma Questionnaire, the Young Schema Questionnaire, and the Temperament and Character Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…First, the literature shows a significant presence of early stress and childhood trauma in patients with FM (Gündüz, 2018; Kaleycheva et al, 2021; Karas et al, 2017; Romeo, Tesio, et al, 2022). Second, previous studies suggest that EMSs maintain stress responses that could facilitate the increase of allostatic overload (da Costa et al, 2020; Vasilopoulou et al, 2020). Third, recent research has found the presence of clinical EMSs in different psychiatric disorders, such as personality disorders (Kunst et al, 2020), anxiety and depression (Bishop et al, 2022), obsessive-compulsive disorder (Khosravani et al, 2021), post-traumatic stress disorder (Zaman et al, 2021), bipolar disorder, and schizophrenia (Khosravani et al, 2021).…”
mentioning
confidence: 99%
“…First, the literature shows a significant presence of early stress and childhood trauma in patients with FM (Gündüz, 2018; Kaleycheva et al, 2021; Karas et al, 2017; Romeo, Tesio, et al, 2022). Second, previous studies suggest that EMSs maintain stress responses that could facilitate the increase of allostatic overload (da Costa et al, 2020; Vasilopoulou et al, 2020). Third, recent research has found the presence of clinical EMSs in different psychiatric disorders, such as personality disorders (Kunst et al, 2020), anxiety and depression (Bishop et al, 2022), obsessive-compulsive disorder (Khosravani et al, 2021), post-traumatic stress disorder (Zaman et al, 2021), bipolar disorder, and schizophrenia (Khosravani et al, 2021).…”
mentioning
confidence: 99%
“…In recent years, J. Panksepp's theory has been linked [29] to, among others, P. Costa and T. McCrae's BIG FIVE theory [78], Cloninger's Temperament and Character Theory [79,80], and even A. Maslow's theory of needs [81]. In their meta-analysis, Marengo et al [82] found that high SEEKING relates to high Openness to Experience, high PLAY to high Extraversion, high CARE/low ANGER to high Agreeableness, and high FEAR/SADNESS/ANGER to high Neuroticism.…”
Section: Neural Emotional Systems and Early Maladaptive Schemas In De...mentioning
confidence: 99%
“…Early negative experiences in the context of attachment bonds are often associated with long-lasting changes in emotional and cognitive processing (i.e., expectancies and beliefs about the self, others and the world) [35]. As a consequence, during childhood or adolescence, maladaptive cognitive and emotional patterns known as Early Maladaptive Schemas (EMSs) develop as a result of these early adverse events [36,37]. EMSs develop as representations of the early child's environment; they in uence the elaboration of later experiences and persist throughout life, directing actions and social interactions with other people [38], as well as shaping personality development [39].…”
mentioning
confidence: 99%